2006
DOI: 10.1111/j.1349-7006.2006.00323.x
|View full text |Cite
|
Sign up to set email alerts
|

A new, simple method for quantifying gemcitabine triphosphate in cancer cells using isocratic high‐performance liquid chromatography

Abstract: A deoxycytidine analog, gemcitabine (dFdC), is effective for treating solid tumors and hematological malignancies. After being transported into cancer cells, dFdC is phosphorylated to dFdC triphosphate (dFdCTP), which is subsequently incorporated into the DNA strand, thereby inhibiting DNA synthesis. Intracellular dFdCTP is the critical determinant for dFdC cytotoxicity, so therapeutic drug monitoring or in vitro testing of the capability of cancer cells to accumulate dFdCTP may be informative for optimizing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…They achieved a satisfactory separation between araCTP, CTP, UTP, ATP, GTP and dFdCTP, however the run time of the analysis was very long (∼2 h). They showed that deoxyribonucleotide triphosphates were eluted at retention times almost identical to those of the corresponding ribonucleotide triphosphates [96].…”
Section: High Performance Liquid Chromatography and Detectionmentioning
confidence: 98%
See 4 more Smart Citations
“…They achieved a satisfactory separation between araCTP, CTP, UTP, ATP, GTP and dFdCTP, however the run time of the analysis was very long (∼2 h). They showed that deoxyribonucleotide triphosphates were eluted at retention times almost identical to those of the corresponding ribonucleotide triphosphates [96].…”
Section: High Performance Liquid Chromatography and Detectionmentioning
confidence: 98%
“…Several chromatographic modes were employed for the determination of the nucleoside gemcitabine monophosphate (dFdCMP), diphosphate (dFdCDP) and triphosphate: either the IE-HPLC [96][97][98], or IP-HPLC [2,58] or RP-HPLC on a PGC column [99]. Veltkamp et al [98] developed an assay based on a weak anion exchange liquid chromatography coupled to a detection with MS/MS detection.…”
Section: High Performance Liquid Chromatography and Detectionmentioning
confidence: 99%
See 3 more Smart Citations